Pengaruh Belanja Online dan Perilaku Konsumtif terhadap Pengeluaran Keuangan Bulanan Gen Z - Dwi Rahmadhani, Oktavia; Fikriyah, Siti Mashlahatul (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the influence of online shopping and consumer behavior on monthly financial expenditure of Generation Z. Using a quantitative approach and multiple linear regression method, data were collected through questionnaires distributed to individuals from Generation Z who have online shopping habits. The results of the analysis show that the regression model built has an F value of 69.720 with a significance of 0.000, indicating a significant relationship between the variables studied. The R Square value of 0.590 indicates that 59% of the variation in Gen Z spending can be explained by online shopping and consumer behavior variables. Partially, online shopping and consumer behavior variables each have a positive influence on spending, with regression coefficients of 0.406 and 0.527, and a significance value of 0.000. These findings emphasize the importance of better financial awareness and financial management among Generation Z to control their spending amidst the increasing trend of digital consumption.